2014
DOI: 10.1128/mbio.00893-14
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the Gut Microbiome following Fecal Microbiota Transplantation

Abstract: Clostridium difficile infection is one of the most common health care-associated infections, and up to 40% of patients suffer from recurrence of disease following standard antibiotic therapy. Recently, fecal microbiota transplantation (FMT) has been successfully used to treat recurrent C. difficile infection. It is hypothesized that FMT aids in recovery of a microbiota capable of colonization resistance to C. difficile. However, it is not fully understood how this occurs. Here we investigated changes in the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
213
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(242 citation statements)
references
References 38 publications
22
213
3
4
Order By: Relevance
“…These results are in agreement with the in vitro and in vivo mouse studies that have previously observed that secondary bile acids, such as lithocholic or deoxycholic acid, inhibit C. difficile growth (20,25). Although the bacterial community is responsible for producing the metabolic environment, it is possible that several types of bacterial communities with similar functions may be capable of the same metabolic outcome, and that structure alone may not be enough to determine recurrence risk (82).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Esupporting
confidence: 81%
“…These results are in agreement with the in vitro and in vivo mouse studies that have previously observed that secondary bile acids, such as lithocholic or deoxycholic acid, inhibit C. difficile growth (20,25). Although the bacterial community is responsible for producing the metabolic environment, it is possible that several types of bacterial communities with similar functions may be capable of the same metabolic outcome, and that structure alone may not be enough to determine recurrence risk (82).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Esupporting
confidence: 81%
“…The intestinal microbiome of children, especially the very young, is known to differ from adults yet there is very little data characterizing associated microbiome changes with FMT in children. Microbiome changes have been reported in a 20-mo-old boy (28), with decreased diversity of the microbiome prior to FMT, with a relative abundance of Proteobacteria, with increased diversity after FMT with increasing Bacteroidetes; these are similar changes to those previously described in adults (39,42). Additionally, in a case series of older children increased microbiome diversity after FMT for CDI appears to be sustained in those without IBD, however at 6 mo decreases to pre-FMT baseline in those with IBD, suggesting IBD hostrelated mechanisms may modify fecal microbiome diversity (29).…”
Section: Fecal Transplant In Childrensupporting
confidence: 71%
“…With the advent of next-generation sequencing, there has been an explosive increase in the use of this phylogenetic marker to characterize microbial communities in the environment and those associated with the body habitats of myriad animal species, including our own. The increasing ease and economy of defining human microbial ecology within and across individuals has spawned many studies that have sought to correlate community membership with health status (3)(4)(5)(6)(7)(8)(9). These studies have highlighted the variation in microbial diversity between body habitats in a given individual and intrapersonal variation in community membership within a given habitat over time, as well as substantial interpersonal differences.…”
mentioning
confidence: 99%